Autologous corneal graft for the treatment of deep corneal defects in dogs: 15 cases (2014‐2017). (1st December 2020) - Jaksz, M.; Fischer, M.‐C.; Fenollosa‐Romero, E.; Busse, C.
Abstract : Objectives: To describe the use of corneal autografts for repair of deep corneal defects in dogs. Materials and Methods: Retrospective analysis of clinical records of dogs that received autologous corneal grafts. Results: Fifteen dogs (16 eyes) of different breed, age and gender were included. Brachycephalic breeds were overrepresented (10/15 dogs). Defects were unilateral in 14 dogs and bilateral in one dog, extended to at least 80% of the stromal thickness in all eyes, with descemetoceles in four eyes and corneal perforations in five eyes. Most ulcers (13/16 eyes) were located centrally. Corneal autografts were harvested from healthy peripheral cornea of the ipsilateral eye. The thickness of the autograft was limited to a set depth of 0.3 mm. The autograft was sutured into a previously debrided ulcer bed with a continuous or simple interrupted suture pattern using absorbable or non‐absorbable suture material. Additional interventions included a partial temporary tarsorrhaphy and bandage contact lenses. Postoperatively patients received topical antibiotics and systemic anti‐inflammatory drugs, and 12/15 dogs also received systemic antibiotics. Mean follow‐up time was 54 days (2 to 462). In all eyes the donor site healed uneventfully with mild, persistent corneal fibrosis. Postoperative complications included autograft keratomalacia, graft dehiscence and corneal pigmentation. No patient required additional surgery. Good structural and functional outcome was accomplished in 14 of 16 eyes. Clinical significance: Autologous corneal grafts provide tectonic support and result in good corneal transparency in selected cases of dogs with deep to perforated corneal ulcerations.